The Effects of Maternal Smoking on Thyroid Function: Findings from Routine First-Trimester Sonographic Anomaly Screening - BAKAR, RABIA ZEHRA; BAKAR R. Z.; ÇETİN, ÇAĞLAR; ÇETİN Ç.; KÜTÜK, MEHMET SERDAR; Yozgat C. Y.; KÜTÜK M. S. (My University, 2023)
Aim This study aimed to assess the effect of tobacco exposure on maternal thyroid function and investigate its relationship to subclinical hypothyroidism in pregnant women during the first trimester. Subjects and Method A comparison of maternal thyroid function was made on 45 smokers, who composed the study group, and 72 non-smokers, pregnant women, who constituted the control group. After determining smokers by questionnaire, carbon monoxide (CO) levels in the expiratory air of the participants in both groups were measured and recorded, and the smokers\" exposure was objectively confirmed. Results Smoking and non-smoking pregnant women were similar regarding body mass index (BMI). While the TSH and fT4 levels were respectively 1.48 mlU/L and 11.43 pmol/L in pregnant women who smoked, that ratio changed to 1.72 mlU/L and 11.17 pmol/L in the non-smokers\" group. But the differences between the groups were not statistically significant (p=0.239, p=0.179). Even though the rate of subclinical hypothyroidism was 8.9% in the smoking group, it was approximately 19.4% in the non-smoker group; the difference was not statistically significant (p=0.187). Conclusion This study proved that there is no statistically significant difference between maternal serum TSH and fT4 levels and the rate of subclinical hypothyroidism in smokers during pregnancy in the first trimester.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Hemşirelik; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Obstetrics and Gynecology; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; KADIN HASTALIKLARI & DOĞUM; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; OBSTETRICS & GYNECOLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Doğum ve Jinekoloji; Annelik ve Ebelik; Pediatrics, Perinatology and Child Health; Maternity and Midwifery; breath carbon monoxide; pregnancy; Smoking; subclinical hypothyroidism; thyrotropin